Analysis of Islamic Finance as a Support Function in Supply Chain Management in Palembang - Ladewi, Yuhanis; Antoni, Antoni; Mizan, Mizan; Melati, Rima (ExcelingTech, 2020)
Abstract- The aim of the study was to find out the finance collection strategy as a support function in supply chain management in the city of Palembang. The variable used in this study is the strategy of collecting finance and optimizing the potential of finance. The data analysis used was qualitative descriptive. The results of the research carried out were the finance collection strategy carried out by the supply chain management in Palembang, namely by establishing finance collection units which were placed in several government agencies such as government agencies and companies as well as cooperating with banks, government officials, and religious leaders. The strategy for collecting finance can be done by OPZ, LAZIS or BAZIS by collecting finance through the payment system, among others; 1) payment of finance with a payroll system, a form of payment of finance by deducting salaries of employees in a company. 2) finance payments via an Android-based E-Card, in this way every Muslim can pay finance via the finance mobile application made by OPZ, LAZIS or BAZIS. 3) Finance can also be paid through Islamic banking services, in this case OPZ, LAZIS or BAZIS can work together with Islamic banking in the process of collecting national finance. As for optimizing the potential for finance collection, finance management institutions in the city of Palembang conduct socialization, promotion and education to the community.